1993
DOI: 10.1038/bjc.1993.321
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione S-transferase expression in benign and malignant ovarian tumours

Abstract: Summary Glutathione S-transferase sub-types a, 1t and were assessed by immunocytochemistry in 109 biopsies of ovarian tissue, comprising malignant epithelial tissue in 86 cases and tissue of ovarian origin considered to be normal in 23. Glutathione S-transferase n was the most prevalent, being present in all except one malignant epithelium studied and 83% of non-malignant tissue. There were no significant differences in the overall distribution of positive staining for a, and in the malignant and non-malignant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
43
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(47 citation statements)
references
References 19 publications
3
43
0
Order By: Relevance
“…In the clinical setting, Green et al (1993) studied GST expression in benign and malignant ovarian tumours and, in agreement with the present study, found that it GST was the most prevalent, being present in the majority of the malignant epithelia and 83% of the non-malignant tissue. There was no significant difference in the overall distribution of positive staining for i, a or p in the malignant and nonmalignant biopsies, although the intensity of staining was greater in malignant epithelia.…”
Section: Immunohistochemical Detection Of Glutathione-s-transferase Esupporting
confidence: 62%
“…In the clinical setting, Green et al (1993) studied GST expression in benign and malignant ovarian tumours and, in agreement with the present study, found that it GST was the most prevalent, being present in the majority of the malignant epithelia and 83% of the non-malignant tissue. There was no significant difference in the overall distribution of positive staining for i, a or p in the malignant and nonmalignant biopsies, although the intensity of staining was greater in malignant epithelia.…”
Section: Immunohistochemical Detection Of Glutathione-s-transferase Esupporting
confidence: 62%
“…However, results contrasting with our study have been found in two further immunohistochemical studies. In the first (Green et al, 1993) the intensity of GST acidic isoenzyme staining was significantly correlated with survival in 78 patients with ovarian carcinoma, the prognosis being poorer in patients with a higher intensity of staining in tumour biopsies. In the second study (Hamada et al, 1994), expression of GST acidic isoenzyme was again examined immunohistochemically in relation to response to chemotherapy in 61 patients with ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
“…GSTs are detoxification enzymes conjugated of glutathione to the electrophilic center of various drugs and resulting in excretion of polar molecules. GSTs are able to metabolized cisplatin, doxorubicin, and melphalan and protecting the cells from environmental or oxidative stress [82].…”
Section: Glutathione-s-transferease (Gst)mentioning
confidence: 99%